Pengembangan pembelajaran Bahasa Indonesia dengan pendekatan cultirally responsive teaching untuk meningkatkan elemen berbicara siswa - Muchson, Ahmad; Widyartono, Didin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study was conducted with the aim of developing an Indonesian language teaching module using a culturally responsive teaching approach, focusing on descriptive text materials to enhance students' speaking skills. The research employed the ADDIE method (analysis, design, development, implementation, and evaluation), which consists of five stages: analysis, design, development, implementation, and evaluation. The teaching module developed in this study is an Indonesian language module for Phase D, intended for ninth-grade junior high school students. It incorporates a culturally responsive teaching approach, using the culture of the Malang region as the content integrated into the module. Learning activities designed following the steps outlined in the module can help students improve their speaking skills. Students from diverse ethnic or cultural backgrounds in the classroom have equal opportunities to develop their speaking abilities. The teaching module developed in this study underwent a series of validation processes, receiving a score of 87.5% from instructional design experts and 80.3% from subject matter experts.